The Effectiveness of Group Counseling with Assertive Training Techniques in Enhancing Self-Esteem among Adolescents Victimized by Bullying - Putri, Fadira; Darmayanti, Nefi (FKIP - Universitas Riau, 2025)
Based on the researcher’s observations at a private vocational high school in Medan, adolescents who were victims of bullying exhibited low levels of self-esteem. Low self-esteem can exacerbate feelings of anxiety, depression, and social isolation, which are often experienced by bullying victims. Bullying itself refers to any form of oppression or violence intentionally carried out by an individual or a stronger group, with the primary aim of harming others, and is typically conducted repeatedly. This study aims to determine whether group counseling using the assertive training technique is effective in enhancing students’ self-esteem. The research employed a quantitative approach with a Quasi-Experimental method using a One-Group Pretest-Posttest Design. The participants consisted of eight students with low self-esteem, selected through purposive sampling. The research instrument used was a self-esteem questionnaire. Data were analyzed using the Wilcoxon Signed Ranks Test, which yielded a Z-value of -2.524 with a p-value of 0.012. Since the p-value < 0.05, the results indicate a significant difference between the pre-test and post-test scores. It can be concluded that group counseling with the assertive training technique is effective in improving self-esteem among adolescents who are victims of bullying.